Portugal e a condenação de Miguel de Molinos : impacto e primeiras reacções - Tavares, Pedro Vilas Boas (1994)
In this article, new documentary evidence is provided on the circulation, reading and consideration of Miguel de Molino’s works in Portugal, as well as some results of a research on the impact on, and the first reactions of Portuguese authorities and devout circles to the Roman trial of the Spanish theologian (18.8.1687).